Chronic Low-Dose Alcohol Consumption Promotes Cerebral Angiogenesis in Mice - Li, Jiyu; Li, Chun; Loreno, Ethyn G.; Miriyala, Sumitra; Panchatcharam, Manikandan; Lu, Xiaohong; Sun, Hong (Frontiers in Cardiovascular Medicine, 2021)
Chronic alcohol consumption dose-dependently affects the incidence and prognosis of ischemic stroke. We determined the influence of chronic alcohol consumption on cerebral angiogenesis under physiological conditions and following ischemic stroke. In in vitro studies, acute exposure to low-concentration ethanol significantly increased angiogenic capability and upregulated vascular endothelial growth factor A (VEGF-A) and vascular endothelial growth factor receptor 2 (VEGFR2) in C57BL/6J mouse brain microvascular endothelial cells (MBMVECs). The increased angiogenic capability was abolished in the presence of a VEGFR2 inhibitor. In addition, the increased angiogenic capability and upregulated VEGF-A and VEGFR2 remained in chronically low-concentration ethanol-exposed MBMVECs. In in vivo studies, 8-week gavage feeding with low-dose ethanol significantly increased vessel density and vessel branches and upregulated VEGF-A and VEGFR2 in the cerebral cortex under physiological conditions. Furthermore, vessel density, vessel branches, and expression of VEGF-A and VEGFR2 in the peri-infarct cortex were significantly greater in low-dose ethanol-fed mice at 72 h of reperfusion. Although low-dose ethanol did not alter cerebral vasoreactivity and regional cerebral blood flow (rCBF) either before or during ischemia, it significantly augmented post-ischemic hyperemia during reperfusion. In contrast, exposure to high-concentration ethanol and 8-week gavage feeding with high-dose ethanol only had a mild inhibitory effect on angiogenic capability and cerebral angiogenesis, respectively. We conclude that heavy alcohol consumption may not dramatically alter cerebral angiogenesis, whereas light alcohol consumption significantly promotes cerebral angiogenesis.